Cerebellar rTMS and PAS effectively induce cerebellar plasticity - Pauly, Martje G.; Steinmeier, Annika; Bolte, Christina; Hamami, Feline; Tzvi, Elinor; Münchau, Alexander; Bäumer, Tobias; Weissbach, Anne (Scientific reports, 2021)
Non-invasive brain stimulation techniques including repetitive transcranial magnetic stimulation (rTMS), continuous theta-burst stimulation (cTBS), paired associative stimulation (PAS), and transcranial direct current stimulation (tDCS) have been applied over the cerebellum to induce plasticity and gain insights into the interaction of the cerebellum with neo-cortical structures including the motor cortex. We compared the effects of 1 Hz rTMS, cTBS, PAS and tDCS given over the cerebellum on motor cortical excitability and interactions between the cerebellum and dorsal premotor cortex / primary motor cortex in two within subject designs in healthy controls. In experiment 1, rTMS, cTBS, PAS, and tDCS were applied over the cerebellum in 20 healthy subjects. In experiment 2, rTMS and PAS were compared to sham conditions in another group of 20 healthy subjects. In experiment 1, PAS reduced cortical excitability determined by motor evoked potentials (MEP) amplitudes, whereas rTMS increased motor thresholds and facilitated dorsal premotor-motor and cerebellum-motor cortex interactions. TDCS and cTBS had no significant effects. In experiment 2, MEP amplitudes increased after rTMS and motor thresholds following PAS. Analysis of all participants who received rTMS and PAS showed that MEP amplitudes were reduced after PAS and increased following rTMS. rTMS also caused facilitation of dorsal premotor-motor cortex and cerebellum-motor cortex interactions. In summary, cerebellar 1 Hz rTMS and PAS can effectively induce plasticity in cerebello-(premotor)-motor pathways provided larger samples are studied.